Erythrina alkaloids from leaves of Erythrina arborescens. Issue 38 (20th September 2019) - Zhang, Bing-Jie; Xiao, Wen-Na; Chen, Jing; Bao, Mei-Fen; Schinnerl, Johann; Wang, Qi; Cai, Xiang-Hai
Abstract: Continued interest in Erythrina alkaloids resulted in the isolation of 38 alkaloids including 7 undescribed ones from the leaves of Erythrina arborescens Roxburgh. Among the new compounds, erythrivarines H-I were two dimeric alkaloids, while others were Erythrina alkaloid glucosides. Dimeric Erythrina alkaloids and monomers, turcomanidine and isoboldine, showed medium xanthine oxidase inhibition. Graphical abstract: Image 1 Highlights: Thirty eight alkaloids including 7 undescribed ones were isolated from leaves of Erythrina arborescens. Their structures were determined by NMR and MS spectroscopic data. Dimeric Erythrina alkaloids and monomers, turcomanidine and isoboldine, showed medium xanthine oxidase inhibition.